2014
DOI: 10.1016/j.biopsycho.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive mood on probabilistic learning: Behavioral and electrophysiological correlates

Abstract: Whether positive mood can change reinforcement learning or not remains an open question. In this study, we used a probabilistic learning task and explored whether positive mood could alter the way positive versus negative feedback was used to guide learning. This process was characterized both at the behavioral and electro-encephalographic levels. Thirty two participants were randomly allocated either to a positive or a neutral (control) mood condition. Behavioral results showed that while learning performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
56
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 47 publications
8
56
6
Order By: Relevance
“…Some studies reported smaller ERN amplitude related to higher life satisfaction (Larson, Good, & Fair, 2010), religiosity, which is linked to a general positive view on life (Inzlicht, McGregor, Hirsh, & Nash, 2009), or to positive affect after watching movie clips (van Wouwe, Band, & Ridderinkhof, 2011). In other studies the opposite pattern was sometimes found: found a larger ERN in a Flanker Task, when the stimuli were overlaid on pleasant IAPS pictures; Bakic, Jepma, De Raedt, & Pourtois (2014) found a larger ERN amplitude during a probabilistic learning task after positive mood induction with guided imagery. Moreover, other studies actually failed to find reliable influence of positive emotions on the size of the ERN component (e.g.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Some studies reported smaller ERN amplitude related to higher life satisfaction (Larson, Good, & Fair, 2010), religiosity, which is linked to a general positive view on life (Inzlicht, McGregor, Hirsh, & Nash, 2009), or to positive affect after watching movie clips (van Wouwe, Band, & Ridderinkhof, 2011). In other studies the opposite pattern was sometimes found: found a larger ERN in a Flanker Task, when the stimuli were overlaid on pleasant IAPS pictures; Bakic, Jepma, De Raedt, & Pourtois (2014) found a larger ERN amplitude during a probabilistic learning task after positive mood induction with guided imagery. Moreover, other studies actually failed to find reliable influence of positive emotions on the size of the ERN component (e.g.…”
mentioning
confidence: 82%
“…A previously validated mood induction procedure (MIP) was used (see Bakic et al, 2014;Vanlessen et al, 2014Vanlessen et al, , 2012. In a between-subjects design either positive or neutral mood was induced by means of an imagery procedure in which participants were instructed to vividly imagine and reexperience a specific autobiographical memory episode (E. A.…”
Section: Mood Inductionmentioning
confidence: 99%
See 3 more Smart Citations